KEEFEKTIFAN MODEL PEMBELAJARAN THREE STEP INTERVIEW DENGAN PENDEKATAN PENDIDIKAN KARAKTER TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS KELAS X MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Rima Nofyani; Venissa Dian Mawarsari; Martyana Prihaswati (Universitas Muhammadiyah Semarang, 2018)
The problem in this study is that students' mathematical communication skills are low because students are not accustomed to writing what was asked of the questions before completing them, so students often misinterpret them when faced with story problems. To overcome theseproblems by applying the Three Step Interview learning model with aneducational approach character. This study aims to determine theeffectiveness of the Three Step Interview learning model with a character education approach to the mathematical communication skills of class X students of SPLDV. This type of experimental research, the population of all class X students at MA Tajul Ulum 2018/2019. Sampling was purposive sampling. The study sample was X MIA I control class, X MIA 2 experimental class and X IIS trial class. The results of the study showed that students achieved complete mathematical communication skills individually: 84.40 and classical: 88.57%. The influence of confidence and communicative on mathematical communication skills is 58.5%, there is a difference in the average of the experimental class: 84.40 and control class: 72.35. It can be concluded that the Three Step Interview model with a character education approach to mathematical communication skills in SPLDV material is effective.Keywords: Three Step Interview, character education, mathematical communication skills.